2019
DOI: 10.4140/tcp.n.2019.317
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between the Medication List in Electronic Prescribing Systems and Patients' Actual Use of Medicines

Abstract: Discrepancies between electronic prescribing systems and patients' actual use of medicines can result in adverse events and medication errors and have serious consequences for the patients. The discrepancies can be identified when performing a thorough medication reconciliation. Computerized health care systems throughout the Danish health care sector are integrated with the Shared Medication Record (SMR). In the SMR, current medication and medication prescriptions are registered. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 0 publications
7
24
3
Order By: Relevance
“…The types of discrepancies found in our study are comparable to other Danish studies [15,16,18,25]. We found that 65% of discrepancies were due to medication being no longer in use, which is similar to results from Bülow et al 2019 [16] and Bülow et al 2021 [15] but higher than results from Buck et al [18].…”
Section: Results In Context Of Other Studiessupporting
confidence: 90%
See 4 more Smart Citations
“…The types of discrepancies found in our study are comparable to other Danish studies [15,16,18,25]. We found that 65% of discrepancies were due to medication being no longer in use, which is similar to results from Bülow et al 2019 [16] and Bülow et al 2021 [15] but higher than results from Buck et al [18].…”
Section: Results In Context Of Other Studiessupporting
confidence: 90%
“…The frequency of discrepancies upon ED admission were lower than what has been observed in other Danish studies [15,16,18]. This may be explained by differences in clinical setting and inclusion criteria.…”
Section: Results In Context Of Other Studiescontrasting
confidence: 74%
See 3 more Smart Citations